Mediale Hybridisierung in Hernando Alvarado Tezozomocs „Crónica Mexicana“ - Richter, Annegret (Linguistik Online, 2017)
The Crónica Mexicana is an account of the Aztec history by Mexica historian Hernando Al-varado Tezozomoc. Written ca. 1598, the chronicle focuses on the journey of the Aztec people, on its mythical origins in Aztlan, its migrations and its military endeavors until becoming the most important power in central Mexico. The work ends with the arrival of the Spaniards in Tlaxcala. In this paper, I analyse how Tezozomoc narrates Aztec history by combining narrative strategies of both Spanish and Aztec origins. I argue that the chronicle can not only be read as an example of the hybridization of different cultural traditions but that it also presents a new understanding of the Spanish colonization by integrating it into a Mesoamerican concept of time.